Rheological Considerations on Polymer-Based Engine Lubricants: Viscosity Index Improvers versus Thickeners—Generalized Newtonian Models. Issue 3 (4th May 2018) - Cusseau, P.; Bouscharain, N.; Martinie, L.; Philippon, D.; Vergne, P.; Briand, F.
ABSTRACT: The development of high-performance lubricants to decrease engine friction and then reduce fuel consumption remains a major challenge for oil manufacturers. Viscosity index improvers (VIIs) are additives used for decades to reduce the dependency of the lubricant's viscosity on temperature to maintain an acceptable lubrication in harsh conditions. Distinction between VIIs and thickeners in realistic engine conditions is of primary interest for oil manufacturers in order to optimize the formulation process. In this context, rheological studies can provide clear insights into the actual effect of such polymeric additives. The behavior of a simplified automotive lubricant is investigated at different temperatures and high pressure and high shear stress and modeling of the properties is proposed. Various polymers of different molecular weights and conformations were mixed in a hydrocracked mineral base oil. The viscosity variations with temperature, pressure, and shear stress, obtained from specific rheometers, were then represented by different models, namely, a Vogel-Fulcher-Tamman expression, a modified Williams-Landel-Ferry correlation, and a Carreau-Yasuda equation. Different rheological responses were observed and allowed the distinction between VIIs and thickeners under different temperature and pressure conditions. The hydrodynamic radii analysis provided an explanation of the rheological responses but also highlighted the limits of the Carreau-Yasuda equation when applied to VIIs. Therefore, the Zhang expression, based on the Maxwell model and applied here to low viscoelastic solutions, is proposed as an appropriate alternative.